Comparing outcomes of ultra-low-cost hearing aids to programmable, refurbished hearing aids for adults with high frequency hearing loss in Malawi: a feasibility study - Parmar, Bhavisha; Phiri, Mwanaisha; Jailos, Louis; Kachapila, Regina; Saleb, Benjamin; Mulwafu, Wakisa; Manchaiah, Vinay; Bhamla, M. Saad (Frontiers in Rehabilitation Sciences, 2023)
Introduction Access to ear and hearing health services are limited or non-existent in low-income countries, with less than 10% of the global production of hearing aids distributed to this population. The aim of this feasibility study was to compare the outcomes of an ultra-low-cost hearing aid (LoCHAid) to programmable, refurbished hearing aids for adults with high-frequency hearing loss, in Blantyre, Malawi. Methods Sixteen adults with high frequency hearing loss, and no prior experience of hearing aids, took part in this study, nine were fitted with the LoCHAid and seven were fitted with refurbished, programmable hearing aids, for a one-month trial. Five standardized hearing qualities questionnaires were used to compare outcomes pre and post device fitting and between devices. Questionnaire scales were analysed using general linear models and inductive thematic analysis was used to evaluate qualitative data. Results Overall, there was no significant difference found between LoCHAid and refurbished hearing aids, and the two device types each showed a similar degree of improvement after fitting. Qualitative data analysis identified two key themes: Sound Quality and User experience. Conclusion The results from this feasibility study are encouraging, but a comprehensive, larger clinical study is needed to draw firm conclusions about the LoCHAid's performance. This study has identified key improvement indicators required to enhance sound quality and user experience of the LoCHAid.